2017
DOI: 10.1371/journal.pone.0172548
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in racial and regional disparities in cervical cancer incidence and mortality in United States

Abstract: BackgroundAlthough black women experienced greater cervical cancer incidence and mortality rate reduction in recent years, they continue to have higher incidence rates than whites. Great variations also exist among geographic regions of the US, with the South having both the highest incidence and mortality rates compared to other regions. The present study explores the question of whether living in the South is associated with greater racial disparity in cervical cancer incidence and mortality by examining rac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
87
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(99 citation statements)
references
References 26 publications
8
87
0
4
Order By: Relevance
“…The incidence rate of cervical cancer is 30% higher in NH black women than in NH white women (Table ) with the largest disparity among older women . The black‐white disparity is even greater when incidence rates are adjusted for hysterectomy prevalence, which is higher in black women . Nevertheless, a faster decline in the cervical cancer incidence rate among NH black women than among white women has substantially narrowed the racial disparity overall and has eliminated it among women younger than 50 years as of the mid‐2000s .…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence rate of cervical cancer is 30% higher in NH black women than in NH white women (Table ) with the largest disparity among older women . The black‐white disparity is even greater when incidence rates are adjusted for hysterectomy prevalence, which is higher in black women . Nevertheless, a faster decline in the cervical cancer incidence rate among NH black women than among white women has substantially narrowed the racial disparity overall and has eliminated it among women younger than 50 years as of the mid‐2000s .…”
Section: Selected Findingsmentioning
confidence: 99%
“…107 The blackwhite disparity is even greater when incidence rates are adjusted for hysterectomy prevalence, which is higher in black women. 108,109 Nevertheless, a faster decline in the cervical cancer incidence rate among NH black women than among white women has substantially narrowed the racial disparity overall and has eliminated it among women younger than 50 years as of the mid-2000s. 30 Declines in cervical cancer incidence and mortality have slowed in black women and stabilized in white women over the last decade (Table 4), perhaps approaching a nadir.…”
Section: Uterine Cervixmentioning
confidence: 99%
“…7 Further, disparities in HPV infection and cervical cancer rates, particularly among black women and those living in the Southern US, persist. 8 Although cervical cancer is preventable through Pap screening and early treatment, vaccination against high-risk HPV types commonly associated with cervical cancer is a promising primary prevention strategy that could reduce cancers, even among women who are not screened according to guidelines. The majority of HPV-related cancers are preventable through HPV vaccination if it is administered before exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas racial disparities in cervical cancer have been described with regard to mortality rates 26 and receipt of standard of care treatment, 27 little is known regarding differences in toxicity experience by racial and ethnic groups. Prior studies have reported that Hispanic women were less likely to experience severe late small bowel toxicity than non-Hispanic white or black women, and this difference was not explained by differences in smoking status or other comorbidities.…”
Section: Discussionmentioning
confidence: 99%